PD-1HIGH Follicular CD4 T Helper Cell Subsets Residing in Lymph Node Germinal Centers Correlate with B Cell Maturation and IgG Production in Rhesus Macaques - Xu, Huanbin; Wang, Xiaolei; Lackner, Andrew A.; Veazey, Ronald S. (Frontiers in Immunology, 2014)
Follicular CD4+ T helper (TFH) cells guide development and maturation of B cells and are crucial for effective antibody responses. Here we found rhesus macaque TFH cells, defined as CXCR5+CD4 T cells, contain two major populations: PD-1INT and PD-1HIGH cells. Of these, PD-1HIGHCD4+ T cells highly co-express ICOS but little CCR7, and reside in lymph node germinal centers, but not in blood. These cells secrete IL-21 and express transcriptional factor-Bcl-6 at higher levels than CXCR5+PD-1INTCD4+ T cells. In addition, the frequency of PD-1HIGHCD4+ T cells is low in lymph nodes of newborns, but increases with age. Levels of PD-1HIGHCD4+ T cells correlate with mature B cells in lymph nodes, and PD-1 blockade in PD-1HIGHCD4+T and B cell co-cultures significantly inhibits IgG production. In summary, PD-1HIGHCD4+ T cells residing in GC represent a specific TFH subset that contributes to maturation of B cells and IgG production.